387 Women's sexuality post gynaecological cancer treatment at groote schuur hospital: a qualitative, descriptive study using a comprehensive framework. (18th September 2019) - Pitcher, S; Fakie, N; Adams, T; van Wijk, L; Saidu, R; Denny, L; Moodley, J
Abstract : Objectives: This study aimed to investigate women's experiences of their sexuality post gynaecological cancer treatment by using a comprehensive framework of sexuality, and, to understand how their sexual health needs can best be addressed as part of cancer care. Methods: The study made use of a qualitative descriptive design. Participants were recruited through purposive sampling at follow-up clinics within Groote Schuur Hospital's Gynae-Oncology Unit. The final sample consisted of 35 women aged 29–35. All women had been diagnosed with one or more gynaecological cancer and treated with either surgery, chemotherapy, radiation or a combination of these. Data was collected using semi-structured, in-depth individual interviews in participants' home language. Pile sorting was used within the interviews to facilitator discussion about difficult topics. The data was analysed using thematic analysis. Results: The results are expected to provide thorough insight into women's sexual functioning and psycho-sexual well-being post treatment and how this affects their lives and relationships. Conclusions: Such information can help develop support programs to improve patients' quality of life post treatment. Furthermore, this research expands the qualitative literature relating to gynaecological cancers in South Africa.